Polypoid melanoma and superficial spreading melanoma different subtypes in the same lesion - Renato Shintani Hikawa; Eliza Sayuri Kanehisa; Mílvia Maria Simões e Silva Enokihara; Mauro Yoshiaki Enokihara; Sérgio Henrique Hirata (Sociedade Brasileira de Dermatologia, 2014)
Melanoma is a malignant melanocytic neoplasm with high mortality rate, and steadily and universally increasing incidence rates. Polypoid melanoma is considered an exophytic variant of the nodular subtype. The incidence of polypoid melanoma is extremely variable, most likely because of the different criteria used for its characterization. We presented a rare case of polypoid melanoma and superficial spreading melanoma in the same lesion.